1981
DOI: 10.1071/ch9811729
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of heterocyclic compounds containing NH, SH and/or OH groups by means of N,N-dimethylformamide dimethyl acetal

Abstract: Methylations of heterocyclic systems, such as benzimidazole, naphth[2,3-c]imidazole, imidazo[4,5-c]-pyridine, purine, pyridine, pyrimidine, pyridazine and s-triazolo[4,3-b]pyridazine, which bore SH, NH and/or OH groups, were carried out with dimethylformamide dimethyl acetal to give the corresponding S-, N- and/or O-methyl derivatives in high yields. Selective methylation of some compounds containing both SH and NH groups took place to give first the S-methyl and subsequently the S,N-dimethyl derivatives. No s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…Reaction of compound 5, independently, with each of dimethyl sulphate (DMS), diethyl sulphate (DES) and benzyl chloride (PhCH 2 Cl) in the presence of K 2 CO 3 , by a simple physical grinding of the reaction mixture in a mortar with a pestle under solvent-free conditions for 10-15 min at room temperature, followed by processing, gave respectively 1-methyl-2-methylthiobenzimi-dazole (6a, i.e., R = CH 3 ), 1-ethyl-2methylthiobenzimidazole (6b, i.e., R = C 2 H 5 ), 1-benzyl-2methylthiobenzimidazole (6c, i.e., R = PhCH 2 ), as the products identical with the ones reported in the earlier methods 9,10 in all respects (m.p. m.m.p.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Reaction of compound 5, independently, with each of dimethyl sulphate (DMS), diethyl sulphate (DES) and benzyl chloride (PhCH 2 Cl) in the presence of K 2 CO 3 , by a simple physical grinding of the reaction mixture in a mortar with a pestle under solvent-free conditions for 10-15 min at room temperature, followed by processing, gave respectively 1-methyl-2-methylthiobenzimi-dazole (6a, i.e., R = CH 3 ), 1-ethyl-2methylthiobenzimidazole (6b, i.e., R = C 2 H 5 ), 1-benzyl-2methylthiobenzimidazole (6c, i.e., R = PhCH 2 ), as the products identical with the ones reported in the earlier methods 9,10 in all respects (m.p. m.m.p.…”
Section: Resultssupporting
confidence: 74%
“…In conclusion, we have developed a green approach for the synthesis of 1-methyl-2-(alkylthio)-1H-benzimidazoles under different conditions. (9,10) m.p. 222-27 0 C) *Yield refers to isolated crude product only; RT: Room temperature m.p.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 However, methylation of NH-containing heterocycles has been less widely reported, these have mainly included amidic-based structures such as uracil derivatives. 4 A notable exception was by B. Stanovnik et al 5 who reported methylation of a number of heterocycles bearing SH, NH, and/or OH groups. DMF-DMA can react via two different pathways, one leading to methylation and the other leading to condensation products such as N,N-dimethyl enaminones (protected formyl group, Scheme 1).…”
mentioning
confidence: 99%
“…It is known from the literature [22] that, in most cases, methylation of cyclic lactams with this reagent takes place at the ring N-atom. Accordingly, one would expected the formation of the N(1)-or N(3)-methylated compounds, or a mixture thereof.…”
mentioning
confidence: 99%